Dynamics of the 2009 A/H1N1 pandemic in the UK, Germany and Spain: An overview of public health interventions and recommendations - Verena Keßler (2013)
Background: In April 2009 a new influenza A/H1N1 virus emerged, causing the first pandemic of the 21st century. The characteristics of the pandemic A/H1N1 virus that decide the size, speed and seriousness of a pandemic were still missing when the virus emerged, but it became clear at an early stage that it met the criteria for a pandemic strain and countries started to take response measures. In order to increase the acceptance of large-scale response measures among the general public and at-risk groups, communication messages have to take into account the factors that influence human behavior. Therefore, a sub-project of the E-com eu project aims to assess the influence of the changing A/H1N1 epidemiology, the changing pattern of risk communication, and the changing official recommendations on human protective behavior during the 2009 A/H1N1 pandemic. This work contributes to the sub-project of the E-com eu project by exploring the dynamics of the 2009 A/H1N1 pandemic in the UK, Germany and Spain. It presents the progress of the pandemic in the UK, Germany and Spain and gives a systematically documented chronological overview of public health measures taken and official recommendations released during the pandemic. A time series analyses explores the interaction of what actually happened (epidemic curves), how the countries responded (public health measures) and what the people were recommended (official recommendations).
Keywords: Influenza A/H1N1; Public Health